Prevalence and Prognostic Value of Left Ventricular Dysfunction in Non-Q-Wave Myocardial Infarction - Palagi, B.; Baroffio, R.; Picozzi, R. (Nuklearmedizin - NuclearMedicine, 1987)
Forty-two consecutive patients with non-Q-wave acute myocardial infarction (AMI) and 40 consecutive patients with transmural AMI were comparatively examined by equilibrium gated radionuclide angiography (ERNA) to assess prevalence and prognostic value of left ventricular dysfunction in non-Q-wave AMI. Left ventricular ejection (LVEF) was generally preserved both in anterior and inferior non-Q-wave infarctions and sharply reduced only in anterior transmural infarctions. ERNA cannot assist in identifying any subgroup of patients with non-Q-wave AMI at risk of major complications other than left ventricular failure because they may develop such complications in spite of a normal LVEF.